Features Of Clinical Course, Diagnostics, Therapy And Evaluation Of The Quality Of Life Of Patients With Chronic Kidney Disease - Daminov Botir Turgunpulatovich,Raimkulova Narina Robertovna, Sabirjanova Zulfia Talgatovna, Tursunbaev Aziz Kamilovich (International Journal of Advanced Science and Technology, 2020)
This article describes the features of the clinical course of the disease, describes the assessmentof the quality of life, diagnostic criteria for the disease, modern classification and tactics ofantihypertensive therapy in patients with chronic kidney disease. Pathogenetic mechanisms of chronickidney disease are revealed. Correspondence of the stages of chronic kidney disease to ICD-10 coding.Various modern studies of assessing the quality of life of patients using the questionnaire are described.SF-36, which includes 8 scales: physical functioning, role-based functioning due to physicalcondition, pain intensity, general health, vital activity, social functioning, role functioning due to theemotional state and mental health.